2015
DOI: 10.1002/jor.22809
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral contact mechanics following a horizontal cleavage lesion in the posterior horn of the medial meniscus

Abstract: The purpose of this study was to determine if a horizontal cleavage lesion (HCL) of the posterior horn of the medial meniscus would result in changes to tibiofemoral contact mechanics, as measured by peak contact pressure and contact area, which can lead to cartilage degeneration. To study this, 10 cadaveric knees were tested in a rig where forces were applied (500 N Compression, 100 N shear, 2.5 Nm Torque) and the knee dynamically flexed from À5˚to 135˚, as peak contact pressure and contact area were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…Terzidis et al7) reviewed 378 isolated meniscal tears in young athletes and found that 22.5% of the tears were HCTs. As HCTs can result in changes in the tibiofemoral contact mechanics that may lead to cartilage degeneration8), it is mandatory to know the characteristics and natural courses of HCTs in younger patients. Causes, clinical features, and natural courses of HCTs in younger patients may differ from those in the middle-aged and elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Terzidis et al7) reviewed 378 isolated meniscal tears in young athletes and found that 22.5% of the tears were HCTs. As HCTs can result in changes in the tibiofemoral contact mechanics that may lead to cartilage degeneration8), it is mandatory to know the characteristics and natural courses of HCTs in younger patients. Causes, clinical features, and natural courses of HCTs in younger patients may differ from those in the middle-aged and elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Macroscopic picture of a specimen stained with ink according to Meachim [31] after tested for 6 h in hyaluronic acid. Left picture 0°p erspective; right picture 90°perspective changes in peak contact pressure and contact area between articulating cartilage [1,2,25]. Becher et al [6] evaluated the effect of various FMI positions on contact pressure in the setting of a complete radial tear of the medial meniscus and found significant increases of peak contact pressure even with flush implant positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Nha et al 13) identified MM root tears in 32.5% of their patients and the prevalence was higher in the MM than in the lateral meniscus, which they attributed to the lesser mobility of the tibial attachment of the posterior horn of the MM than that of the lateral meniscus. On the other hand, Arno et al 14) suggested that changes in the tibiofemoral contact mechanics could result in articular cartilage degeneration in knees with horizontal cleavage lesions unaccompanied by loss of hoop tension.…”
Section: Discussionmentioning
confidence: 99%